Endocrine Diseases: Types, Causes And Treatment Methods - Shokirova, Rukhsorakhon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This article comprehensively reviews human endocrine diseases, their causes, clinical manifestations, diagnostic methods, and modern treatment strategies. Preventive measures and epidemiological data are also included.